PENGELOLAAN KAS DAN SETARA KAS YANG OPTIMAL DALAM RANGKA MENINGKATKAN PROFITABILITAS PADA PT. SELECTA BATU - Ady Warsito Rachman; Nur Khusniyah Indrawati (Jurnal Ilmiah Mahasiswa FEB, 2012)
Cash management  includes  the  efficient  collection,  payment of  cash  and  temporary investments  in marketable securities. This study aims to determine the management of cash and cash equivalents in order to improve  profitability  in the  PT  Selecta  and  whether  management of  cash  and  cash equivalents are carried out is optimal. Object of this study is the PT Selecta Batu. The results showed, cash management and cash equivalents are carried out by PT Selecta has not been optimal. In 2011, when  the company's liquidity  is  high  due to  large  cash  holdings,  cash  turnover  actually decreased from the previous year. That is because the PT Selecta has not been idle cash invested in marketable securities,  so that the  profit earned  is not maximized.  To  obtain  optimality  in  cash management, investing idle cash can be made through securities firms, one of which is the product of PT Danareksa Sekuritas, Reksa Dana Seruni Pasar Uang III that has a consistent level of return ride. Keyword : Cash Management, Idle Cash, Securities, Cash Inflow, Cash Outflow.